The discovery of BMS-737 as a potent, CYP17 lyase-selective inhibitor for the treatment of castration-resistant prostate cancer. (1st November 2022) - Padmakar Darne, Chetan; Velaparthi, Upender; Saulnier, Mark; Frennesson, David; Liu, Peiying; Huang, Audris; Tokarski, John; Fura, Aberra; Spires, Thomas; Newitt, John; Spires, Vanessa M.; Obermeier, Mary T.; et al.
Graphical abstract: Abstract: We report herein, the discovery of BMS-737 (compound 33 ) as a potent, non-steroidal, reversible small molecule inhibitor demonstrating 11-fold selectivity for CYP17 lyase over CYP17 hydroxylase, as well as a clean xenobiotic CYP profile for the treatment of castration-resistant prostate cancer (CRPC). Extensive SAR studies on the initial lead 1 at three different regions of the molecule resulted in the identification of BMS-737, which demonstrated a robust 83% lowering of testosterone without any significant perturbation of the mineralocorticoid and glucocorticoid levels in cynomologous monkeys in a 1-day PK/PD study.